Low-moisture-absorption high-yellowing-resistance PPA material and preparation method thereof

A low-hygroscopic and high-yellowing-resistant PPA material is developed using PA resin and additives to address yellowing and water absorption issues in electronic connectors, ensuring stability and flexibility.

CN119192835AActive Publication Date: 2024-12-27GUANGDONG DEFA HIGH-TECH MATERIALS CO LTD

Patent Information

Application Number
CN202411363966.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-28
Publication Date
2024-12-27
Estimated Expiration
2044-09-28

AI Technical Summary

Technical Problem

Polyamide resin used in electronic connectors is prone to yellowing, water absorption, and blistering during high-temperature reflow soldering, leading to reduced stability and cracking due to the addition of glass fiber and mineral filler, which increases brittleness.

Method used

A low-hygroscopic and high-yellowing-resistant PPA material is prepared using PA resin, rosin-modified maleic acid resin, tetrapolyricinoleate, dibutyl itaconate, and silane coupling agent, along with glass fiber and mineral filler, forming a hydrophobic interwoven system to enhance water resistance and flexibility, and adding antioxidants for improved stability.

Benefits of technology

The PPA material exhibits excellent mechanical properties, low water absorption, high yellowing resistance, and good toughness, maintaining stability during temperature changes without cracking.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005065669760000011
    Figure BDA0005065669760000011
  • Figure BDA0005065669760000051
    Figure BDA0005065669760000051
  • Figure BDA0005065669760000061
    Figure BDA0005065669760000061
Patent Text Reader

Abstract

The invention relates to the field of functional plastic materials, and discloses a low-moisture-absorption high-yellowing-resistance PPA material and a preparation method thereof. The low-moisture-absorption and high-yellowing-resistance PPA material is prepared from the following raw materials in parts by weight: 50-70 parts of PPA resin, 32-42 parts of glass fibers, 10-20 parts of mineral filler, 25-35 parts of hydrophobic nylon resin, 5-8 parts of a flame retardant and 1-3 parts of an antioxidant. The hydrophobic nylon resin is prepared from PA (Polyamide) resin, rosin modified maleic resin, tetrameric ricinoleate, dibutyl itaconate and a silane coupling agent; the preparation method comprises the following steps: mixing the PPA resin, the hydrophobic nylon resin, the glass fiber, the mineral filler, the flame retardant and the antioxidant, performing melt extrusion, cooling and drying. And dicing. The preparation process is simple, and the prepared PPA material has relatively good water resistance and yellowing resistance, has relatively good welding stability and temperature-resistant stability when being applied to an electronic connector, and is not easy to crack.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of functional plastic materials, and more specifically, to a low-hygroscopic and highly anti-yellowing PPA material and a preparation method thereof. Background Art

[0002] Polyamide resin (PA for short, commonly known as nylon) has excellent properties such as light weight, heat resistance, wear resistance, and chemical corrosion resistance. These properties make polyamide resin widely used in the field of electronics and electrical appliances, such as in electronic connectors.

[0003] During the application process, electronic connectors need to be connected to PCB boards through high-temperature reflow soldering process. The temperature of high-temperature reflow soldering can generally reach up to 240-280℃. Electronic connectors are prone to yellowing and water absorption and blistering under continuous high temperature conditions, which reduces the processing stability and use stability of electronic connectors.

[0004] In order to improve the problem of polyamide resin easily turning yellow and bubbling due to water absorption in electronic connectors, some glass fiber and mineral filler are generally added to the polyamide resin to improve the density and dimensional stability of the polyamide resin and reduce the channels for water penetration, thereby reducing water absorption and improving oxidation resistance; at the same time, glass fiber and mineral filler can also improve the mechanical strength of polyamide resin, but the addition of glass fiber and mineral filler will increase the brittleness of polyamide resin. During high-temperature reflow soldering, the electronic connector is locally heated or cooled, and the welding parts are prone to cracking, which reduces the stability of use in the electronic connector. Summary of the invention

[0005] In order to solve the problem that polyamide resin is used in electronic connectors and is prone to yellowing, water absorption and blistering, and local cracking during high-temperature reflow soldering, the present application provides a low-hygroscopic and high-yellowing-resistance PPA material and a preparation method thereof.

[0006] In the first aspect, the present application provides a low-hygroscopicity and high-yellowing-resistance PPA material, which adopts the following technical solution: A low-hygroscopic and high-anti-yellowing PPA material is prepared from the following raw materials in parts by weight: The hydrophobic nylon resin consists of PA resin, rosin-modified maleic acid resin, tetrapolyricinoleic acid ester, dibutyl itaconate and a silane coupling agent.

[0007] By adopting the above technical scheme, PPA resin has excellent mechanical properties, heat resistance, creep resistance and fatigue resistance, low water absorption and good processing fluidity. The present application uses PPA resin as the resin system, and adds glass fiber and mineral filler as reinforcing agents to the PPA resin, which can improve the structural density of the resin system, thereby improving the water resistance and yellowing resistance of the prepared PPA material; however, the addition of glass fiber and mineral filler causes the problem of uniform dispersion in the resin system, and the prepared PPA material has large rigidity and brittleness, and is prone to cracking. Therefore, the present application further adds a hydrophobic nylon resin prepared from PA resin, rosin-modified maleic acid resin, tetrapolyricinoleate, dibutyl itaconate and silane coupling agent; PA resin has low cost and excellent mechanical properties, but the hydrophilic groups (such as amino groups and amide groups) in PA resin can react with water. The molecules form hydrogen bonds, which makes the PA resin water-absorbent. Therefore, the present application adds rosin-modified maleic acid resin, tetrapolyricinoleate, dibutyl itaconate and silane coupling agent to the PA resin, and the four produce a good synergistic effect to form an interwoven system with good hydrophobicity, which can make the PA resin evenly adsorbed and dispersed in the interwoven system. The prepared hydrophobic nylon resin has excellent flexibility, water resistance and dispersibility, and can further improve the compatibility of PPA resin, glass fiber and mineral filler. There is no need to add additional compatibilizers. The prepared PPA material has good water resistance and yellowing resistance, as well as good toughness. It is used in electronic connectors, has good welding stability, is not easy to absorb water or yellow; has good aging resistance and is not easy to crack; the antioxidant can be evenly dispersed in the resin system, further improving the yellowing resistance of the prepared PPA material.

[0008] Preferably, the hydrophobic nylon resin is prepared from the following raw materials in parts by weight: PA resin 60-80 parts Rosin modified maleic acid resin 10-20 parts 8-12 parts of tetrapolyricinoleate 6-10 parts of dibutyl itaconate Silane coupling agent 4-6 parts.

[0009] By adopting the above technical scheme, the PA resin is mixed and modified with optimal amounts of rosin-modified maleic acid resin, tetrameric castor oil ester, dibutyl itaconate and silane coupling agent, which has a good synergistic effect. Under the synergistic penetration of tetrameric castor oil ester and dibutyl itaconate, the PA resin fully melts and expands, and is dispersed and interwoven in the hydrophobic system formed by the rosin-modified maleic acid resin and the silane coupling agent. The prepared hydrophobic nylon resin has excellent flexibility, water resistance and yellowing resistance, and can be further dispersed in the resin system to form a uniform hydrophobic dense structure, thereby improving the water resistance, yellowing deformation resistance and temperature stability of the prepared PPA material, and is not easy to crack.

[0010] Preferably, the PA resin is PA-66 and / or PA-6.

[0011] By adopting the above technical scheme, the above PA resin has good mechanical properties and its cost is lower than other PA resins. However, the water absorption rate of the above PA resin is relatively high. Therefore, by mixing and modifying the above PA resin, the water resistance of the PA resin is greatly improved. While reducing the production cost, the water resistance and yellowing resistance of the prepared PPA material can be improved, which is suitable for industrial continuous production.

[0012] Preferably, the silane coupling agent is composed of n-octyltrimethoxysilane and tetrakis(dimethylvinylsiloxy)silane in a weight ratio of 1:(1-3).

[0013] By adopting the above technical scheme, n-octyltrimethoxysilane containing a long straight-chain alkyl group is compounded with tetrakis(dimethylvinylsiloxy)silane, and the branched siloxy groups and four branched vinyl groups in the molecular structure of tetrakis(dimethylvinylsiloxy)silane are interwoven and dispersed to form a network-like dispersed hydrophobic system, so that the PA resin is evenly interwoven and dispersed in the system of the silane coupling agent, which can further improve the water resistance and yellowing resistance of the hydrophobic nylon resin, thereby improving the flexibility, water resistance and yellowing resistance of the prepared PPA material, and having good temperature resistance and stability and not easy to crack.

[0014] Preferably, the hydrophobic nylon resin is prepared by the following steps: PA resin, rosin-modified maleic acid resin, tetrapolyricinoleate, dibutyl itaconate and a silane coupling agent are mixed, melt-extruded, cooled, dried and granulated to prepare a hydrophobic nylon resin.

[0015] By adopting the above technical solution, various raw materials are mixed and melt-extruded to obtain a hydrophobic nylon resin with stable performance.

[0016] Preferably, the melting temperature is 240-270°C.

[0017] By adopting the above technical solution, the optimal melting temperature can make the components uniformly mixed and melted, and prepare a hydrophobic nylon resin with a uniform dispersion system.

[0018] Preferably, the glass fiber is alkali-free glass fiber and / or medium-alkali glass fiber; the mineral filler is one or a combination of calcium carbonate, kaolin, wollastonite and talc.

[0019] By adopting the above technical scheme, the above-mentioned glass fiber and mineral filler have good mechanical strength, rigidity and fatigue resistance. When added to the resin system, they can fill and reinforce the molecular chain segments of the resin system, improve the density of the material, reduce the shrinkage rate, and thereby reduce the hygroscopicity and yellowing properties of the prepared PPA material while improving the flame retardancy.

[0020] Preferably, the flame retardant is an ammonium phosphate flame retardant and / or a phosphazene flame retardant.

[0021] By adopting the above technical solution, the above flame retardant has good flame retardant properties and can improve the flame retardancy of the prepared low-hygroscopic and high-yellowing resistance PPA material.

[0022] Preferably, the antioxidant is composed of a hydroxylamine antioxidant, a hindered amine antioxidant and a benzofuranone antioxidant in a weight ratio of 1:(1-2):(0.5-1).

[0023] By adopting the above technical scheme, the hydroxylamine antioxidant, hindered amine antioxidant and benzofuranone antioxidant in an optimal dosage ratio work synergistically, have good color protection, high compatibility, low volatility and stable high-temperature storage, and perform particularly well as a stabilizer in melt processing. It is suitable for the resin system of this application and can further improve the yellowing resistance of the prepared PPA material.

[0024] In the second aspect, the present application provides a method for preparing a low-hygroscopic and high-yellowing-resistant PPA material, using the following technical solution: A method for preparing a low-hygroscopic and high-yellowing-resistant PPA material comprises the following preparation steps: PPA resin and hydrophobic nylon resin are added to a mixing device, and after mixing evenly, glass fiber, mineral filler, flame retardant and antioxidant are added and mixed evenly, melt-extruded, cooled, dried and pelletized to obtain a low-hygroscopic and highly yellowing-resistant PPA material.

[0025] By adopting the above technical solution, the various raw materials are mixed and melt-extruded to produce a PPA material with stable performance, low moisture absorption and high yellowing resistance.

[0026] In summary, this application has the following beneficial effects: 1. The low moisture absorption and high yellowing resistance PPA material of the present application is made of PPA resin, glass fiber, mineral filler, hydrophobic nylon resin, flame retardant and antioxidant. The hydrophobic nylon resin is made of rosin-modified maleic acid resin, tetrapolyricinoleate, dibutyl itaconate and silane coupling agent. The prepared PPA material has good water resistance and yellowing resistance as well as good toughness. It is used in electronic connectors, has good welding stability, is not easy to absorb water or yellow, has good aging resistance and is not easy to crack.

[0027] 2. The use of a silane coupling agent composed of n-octyltrimethoxysilane and tetrakis(dimethylvinylsiloxy)silane can further improve the water resistance and yellowing resistance of the hydrophobic nylon resin, while improving the dispersibility of glass fiber and mineral filler in the resin system, further improving the comprehensive performance of the PPA material.

[0028] 3. The antioxidant composed of hydroxylamine antioxidant, hindered amine antioxidant and benzofuranone antioxidant can be evenly dispersed in the resin system of the present application, and has a good synergistic effect with the hydrophobic nylon resin, further improving the yellowing resistance of the prepared PPA material. DETAILED DESCRIPTION

[0029] The present application is further described in detail below with reference to the embodiments.

[0030] The following are the sources and specifications of some raw materials of this application. The raw materials used in the preparation examples and embodiments of this application can be obtained from the market, including but not limited to the raw materials of the following models and manufacturers. Raw materials with equivalent performance can be used: 1. PPA resin: DuPont HTN502; 2. Glass fiber: Jushi Group, alkali-free glass fiber: diameter 10-20μm, fiber length 1-3mm; medium-alkali glass fiber: diameter 10-20μm, fiber length 1-3mm; 3. Mineral filler: Calcium carbonate: light calcium carbonate, 800-1250 mesh; Kaolin: calcined kaolin, 800-1250 mesh; Talc: 800-1250 mesh; 4. PA resin: PA6: DuPont 7331J; PA66: Asahi Kasei 1300S; PA612: DuPont 157HSL; 5. Rosin modified maleic acid resin: Model 422; 6. Tetrapolyricinoleate: kinematic viscosity 250-450cst / ℃, acid value 45-65KOHmg / g, Hongli Chemical; 7. Dibutyl itaconate: CAS No. 2155-60-4, content 99%; 8. Hydroxylamine antioxidant: Qitai Chemical, Revonox 420V; 9. Hindered amine antioxidant: antioxidant 5057 or antioxidant T-557; 10. Benzofuranone antioxidant: Qitai Chemical, Revonox501.

[0031] Preparation Example of Hydrophobic Nylon Resin Preparation Example 1 6kgPA-66 as PA resin, 2kgrosin modified maleic acid resin, 0.8kg tetrapolyricinoleate, 1kg dibutyl itaconate and 0.4kg dodecyltrimethoxysilane as silane coupling agent were mixed, and a twin-screw extruder was used. The extrusion pressure was adjusted to 80MPa, the screw speed was 20r / min, the temperature of the first zone of the barrel was 240°C, the temperature of the second zone was 250°C, the temperature of the third zone was 265°C, the temperature of the die head was 260°C, and the hydrophobic nylon resin was obtained by melt extrusion, water cooling, hot air drying and pelletizing.

[0032] Preparation Example 2-3 The difference between Preparation Example 2-3 and Preparation Example 1 is that the amount of raw materials used and the preparation parameters are different, see Table 1 below for details.

[0033] Table 1 Raw material dosage and preparation conditions of Preparation Examples 1-3 Preparation Example 4 The difference between Preparation Example 4 and Preparation Example 1 is that the type of silane coupling agent is different. The silane coupling agent in Preparation Example 4 is composed of n-octyltrimethoxysilane and tetrakis(dimethylvinylsiloxy)silane, the amount of n-octyltrimethoxysilane is 0.2kg, the amount of tetrakis(dimethylvinylsiloxy)silane is 0.2kg, and the others are the same as Preparation Example 1.

[0034] Preparation Example 5 The difference between Preparation Example 5 and Preparation Example 4 is that the amount of octyltrimethoxysilane used is 0.1 kg, the amount of tetrakis(dimethylvinylsiloxy)silane used is 0.3 kg, and the rest is the same as Preparation Example 1.

[0035] Preparation Comparative Example 1 The difference between Preparation Comparative Example 1 and Preparation Example 1 is that the rosin-modified maleic acid resin is replaced by an equal amount of terpene resin, the terpene resin has a CAS number of 9003-74-1, a content of 99%, and a model of T100, and the rest is the same as Preparation Example 1.

[0036] Preparation Comparative Example 2 The difference between Preparation Comparative Example 2 and Preparation Example 1 is that an equal amount of tetrapolyricinoleate is replaced by ethylene dioleic acid amide, and ethylene dioleic acid amide is Crodamide EBO produced by Croda Chemical, and the rest is the same as Preparation Example 1.

[0037] Preparation Comparative Example 3 The difference between Preparation Comparative Example 3 and Preparation Example 1 is that an equal amount of dibutyl itaconate is replaced by dioctyl phthalate, and the rest is the same as Preparation Example 1.

[0038] Preparation Comparative Example 4 The difference between Preparation Comparative Example 4 and Preparation Example 1 is that an equal amount of tetrapolyricinoleate is replaced by dibutyl itaconate, and the rest is the same as Preparation Example 1. Example

[0039] Example 1 Example 1 discloses a low-hygroscopicity and high-yellowing-resistance PPA material, which is prepared by the following steps: 5kg of PPA resin and 2.5kg of the hydrophobic nylon resin obtained in Preparation Example 1 were added to a mixing device, mixed at a temperature of 180°C for 30 minutes, and after mixing evenly, 3.2kg of alkali-free glass fiber as glass fiber, 1kg of calcium carbonate as a mineral filler, 0.5kg of ammonium phosphate as a flame retardant and 0.2kg of antioxidant (composed of antioxidant 1010 and antioxidant 168 in a weight ratio of 1:1) were added and mixed evenly. A twin-screw extruder was used, and the extrusion pressure was adjusted to 90MPa, the screw speed was 30r / min, the temperature of zone 1 of the barrel was 290°C, the temperature of zone 2 was 315°C, the temperature of zone 3 was 330°C, the temperature of the die head was 310°C, and melt extrusion, water cooling, hot air drying and pelletizing were carried out to obtain a low-hygroscopic and high-yellowing resistance PPA material.

[0040] Example 2-3 The difference between Example 2-3 and Example 1 is that the amount of raw materials used and the preparation conditions are different, and the source of the hydrophobic nylon resin is also different, see Table 2 below for details.

[0041] Table 2 The amount of raw materials, preparation conditions and sources of hydrophobic nylon resin in Examples 1-3 Embodiment 4-5 The difference between Example 4-5 and Example 1 is that the sources of the hydrophobic nylon resin are different, see Table 3 below for details.

[0042] Table 3 Sources of hydrophobic nylon resins of Examples 4-5 Example Source of hydrophobic nylon resin Example 4 Preparation Example 4 Example 5 Preparation Example 5 Example 6 The difference between Example 6 and Example 5 is that the antioxidants are different. The antioxidants in Example 7 are composed of hydroxylamine antioxidant, hindered amine antioxidant and benzofuranone antioxidant. The amount of hydroxylamine antioxidant is 0.08 kg, the amount of hindered amine antioxidant (antioxidant 5057) is 0.08 kg, and the amount of benzofuranone antioxidant is 0.04 kg. The rest is the same as Example 5.

[0043] Example 7 The difference between Example 7 and Example 6 is that the amount of hydroxylamine antioxidant used is 0.05 kg, the amount of hindered amine antioxidant (antioxidant T-557) used is 0.1 kg, the amount of benzofuranone antioxidant used is 0.05 kg, and the rest is the same as Example 6.

[0044] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the hydrophobic nylon resin is replaced by an equal amount of PA612 resin, and the rest is the same as Example 1.

[0045] Comparative Examples 2-5 The difference between Comparative Examples 2-5 and Example 1 is that the sources of the hydrophobic nylon resin are different, as shown in Table 4 below.

[0046] Table 4 Sources of hydrophobic nylon resins of Comparative Examples 1-5 Comparative Example Source of hydrophobic nylon resin Comparative Example 2 Preparation Comparative Example 1 Comparative Example 3 Preparation Comparative Example 2 Comparative Example 4 Preparation Comparative Example 3 Comparative Example 5 Preparation Comparative Example 4 Performance Testing The following performance tests were conducted on the low-hygroscopicity and high-anti-yellowing PPA materials obtained in Examples 1-7 and Comparative Examples 1-5: The low-hygroscopic and high-anti-yellowing PPA material was injection molded to prepare a test piece, and the specification of the test piece was length*width*height=5cm*3cm*0.2cm; 1. Hygroscopicity test: Place the test piece in a constant temperature and humidity chamber at 250°C and 85% humidity for 48 hours, wipe it dry, calculate the weight change rate of the test piece, record it as water absorption (unit: %), test and record the test results; 2. Yellowing test: Place the test piece in a constant temperature and humidity chamber at 250°C and 85% humidity for 7 days, use a colorimeter to measure the color difference before and after the test, and test and record the test results; 3. Anti-cracking test: Place the test piece in a constant temperature and humidity box at 250°C and 85% humidity for 1 day. Immediately place it in a refrigerator at -10°C for 1 day. Repeat this test procedure 7 times. After returning to room temperature, observe whether there are cracks on the surface of the test piece and record the test results. The following are the performance test data of the low-hygroscopicity and high-yellowing-resistance PPA materials prepared in Examples 1-7 and Comparative Examples 1-5, see Table 5 below for details.

[0047] Table 5 Performance data of Examples 1-7 and Comparative Examples 1-5 Combining Examples 1-3 and Examples 4-5, Comparative Examples 1-5 and Table 5, it can be concluded that the PPA material prepared by using the hydrophobic nylon resin composed of PA resin, rosin-modified maleic acid resin, tetrapolyricinoleate, dibutyl itaconate and silane coupling agent of the present application has low water absorption and good anti-yellowing performance, and will not crack after high temperature and low temperature change tests. In Example 4-5, compared with Example 1, n-octyltrimethoxysilane and tetra(dimethylvinylsiloxy)silane are used as the silane coupling agent system, and the two have a good synergistic effect. The water absorption rate of the prepared PPA resin is reduced by 0.09%, and the color difference is reduced by 0.1; in Comparative Examples 2-5, compared with Example 1, the water absorption rate of the prepared PPA resin is significantly improved from 0.13% to a maximum of 0.5%, the anti-yellowing performance is significantly reduced, and the color difference is increased from 0.43 to 1.04. After high and low temperature tests, cracks appear. It can be seen that the PA resin, rosin-modified maleic acid resin, and tetra(dimethylvinylsiloxy)silane with a better dosage ratio are more Polyricinoleate, dibutyl itaconate and silane coupling agent have good synergistic effect, which can improve the density and toughness of the resin system, while improving the dispersion uniformity of the antioxidant, thereby improving the water resistance, yellowing resistance and cracking resistance of the prepared PPA resin; while in Comparative Example 1, the hydrophobic nylon resin was replaced with PA612 resin, and the water resistance and yellowing resistance of the prepared PPA resin were reduced, and obvious cracks appeared after high and low temperature tests. This may be because the dispersion uniformity and structural density of the resin system were reduced, which increased the rigidity of the PPA resin, and the unevenly dispersed system was prone to water absorption and yellowing problems.

[0048] Combining Example 5 and Examples 6-7 with Table 5, it can be concluded that the use of the hydroxylamine antioxidant, hindered amine antioxidant and benzofuranone antioxidant in the preferred dosage ratio of the present application as an antioxidant has a good synergistic effect and is more suitable for the resin system of the present application, and can further enhance the yellowing resistance of the prepared PPA resin.

[0049] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A low-hygroscopic and high-anti-yellowing PPA material, characterized in that: Made from the following raw materials in parts by weight: PPA resin 50-70 parts Glass fiber 32-42 parts Mineral filler 10-20 parts 25-35 parts of hydrophobic nylon resin Flame retardant 5-8 parts 1-3 parts of antioxidants; The hydrophobic nylon resin consists of PA resin, rosin-modified maleic acid resin, tetrapolyricinoleic acid ester, dibutyl itaconate and a silane coupling agent.

2. The low-hygroscopic and high-yellowing-resistance PPA material according to claim 1, characterized in that: The hydrophobic nylon resin is prepared from the following raw materials in parts by weight: PA resin 60-80 parts Rosin modified maleic acid resin 10-20 parts 8-12 parts of tetrapolyricinoleate 6-10 parts of dibutyl itaconate Silane coupling agent 4-6 parts.

3. A low-hygroscopic and high-yellowing-resistance PPA material according to claim 2, characterized in that: The PA resin is PA-66 and / or PA-6.

4. The low-hygroscopic and high-yellowing-resistance PPA material according to claim 2, characterized in that: The silane coupling agent is composed of n-octyltrimethoxysilane and tetrakis(dimethylvinylsiloxy)silane in a weight ratio of 1:(1-3).

5. A low-hygroscopicity and high-yellowing-resistance PPA material according to any one of claims 2 to 4, characterized in that: The hydrophobic nylon resin is prepared by the following steps: PA resin, rosin-modified maleic acid resin, tetrapolyricinoleate, dibutyl itaconate and a silane coupling agent are mixed, melt-extruded, cooled, dried and granulated to prepare a hydrophobic nylon resin.

6. The low-hygroscopic and high-anti-yellowing PPA material according to claim 5, characterized in that: The melting temperature is 240-270°C.

7. The low-hygroscopic and high-anti-yellowing PPA material according to claim 1, characterized in that: The glass fiber is alkali-free glass fiber and / or medium-alkali glass fiber; the mineral filler is one or a combination of calcium carbonate, kaolin, wollastonite and talc.

8. The low-hygroscopic and high-anti-yellowing PPA material according to claim 1, characterized in that: The flame retardant is an ammonium phosphate flame retardant and / or a phosphazene flame retardant.

9. The low-hygroscopic and high-yellowing-resistance PPA material according to claim 1, characterized in that: The antioxidant consists of a hydroxylamine antioxidant, a hindered amine antioxidant and a benzofuranone antioxidant in a weight ratio of 1:(1-2):(0.5-1).

10. A method for preparing a low-hygroscopic and high-yellowing-resistance PPA material according to any one of claims 1 to 9, characterized in that: The method comprises the following preparation steps: PPA resin and hydrophobic nylon resin are added to a mixing device, and after mixing evenly, glass fiber, mineral filler, flame retardant and antioxidant are added and mixed evenly, melt-extruded, cooled, dried and pelletized to obtain a low-hygroscopic and highly yellowing-resistant PPA material.

Citation Information

Patent Citations

  • Low-water absorption high-rigidity nylon composite material and preparation method thereof

    CN104262957A

  • Hydrophobic aluminum electrode anticorrosive coating and preparation method thereof

    CN105820610A

  • Hydrolysis-resistant and high-temperature-resistant polyamide composite material and method for preparing same

    CN108264760A

  • High-temperature-resistant halogen-free flame-retardant PPA composite material and preparation method thereof

    CN113736253A

  • Emulsion ink for stencil printing

    JP2009270070A

Cited By

  • Anti-edge-scattering high-strength nylon braid for intelligent wearing and preparation method of anti-edge-scattering high-strength nylon braid

    CN120985910A

  • Intelligent wear anti-fraying high-strength nylon braid and preparation method thereof

    CN120985910B